2000
DOI: 10.4269/ajtmh.2000.63.1
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity associated with Schistosoma mansoni infection determined by ultrasound in an endemic area of Brazil, Caatinga do Moura.

Abstract: Abstract. Morbidity in schistosomiasis is caused by a granulomatous response to Schistosoma mansoni eggs deposited in peripheral portal veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…Jesus et al 10 observed in hepatosplenic patients a correlation between the echogenicity of the portal tract and spleen size. Our data also showed that the portal and splenic vein diameters were slightly larger in G3 and G4 groups but these results were not statistically significant.…”
Section: Discussionmentioning
confidence: 96%
“…Jesus et al 10 observed in hepatosplenic patients a correlation between the echogenicity of the portal tract and spleen size. Our data also showed that the portal and splenic vein diameters were slightly larger in G3 and G4 groups but these results were not statistically significant.…”
Section: Discussionmentioning
confidence: 96%
“…For three patients, the fibrosis had changed from degree 0 to I, and for nine patients, the fibrosis had changed from degree I to II. One year after treatment with oxaminiquine, all patients had improved and returned to degree 0 or I of fibrosis (12).…”
Section: Methodsmentioning
confidence: 94%
“…This classification defines hepatic fibrosis as degree 0 if the periportal tract thickness is Ͻ3 mm, as degree I if it is 3 to 5 mm thick, as degree II if it is Ͼ5 to 7 mm thick, and as degree III if it is Ͼ7 mm thick. The examinations were performed by two independent persons, and a correlation between periportal thickness and portal vein diameter and spleen size was demonstrated (12). Twenty-one subjects who went untreated, even after several attempts to locate them for treatment with schistosomicidal drugs, were reevaluated by ultrasonographic exam 1 year after the first evaluation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It represents an important indirect method of diagnosis and classification of the disease (Abdel-Latif et al 1981, Hussain et al 1984, Fataar et al 1984, Cerri et al 1984, Homeida et al 1988a, b, Abdel-Wahab et al 1989, PintoSilva et al 1994, Gerspacher-Lara et al 1998, GerspacherLara 1999, Niamey Working Group 2000, Ritcher et al 2001. US has also been used as a tool in the evaluation of therapeutic response and regression of fibrosis in schistosomiasis (Massoud et al 1986, Homeida et al 1988c, Homeida et al 1991, DoehringSchwerdtfeger et al 1992, Boisier et al 1998, Frenzel et al 1999, De Jesus et al 2000, Cota et al 2006. Ultrasonographic examination of subjects with hepatosplenic schistosomiasis has detected a characteristic pattern of abnormalities, quite different from the aspects observed in liver cirrhosis (Homeida et al 1988a, Abdel-Wahab et al 1989) and in acute schistosomiasis (Barata et al 1999, 1997.…”
mentioning
confidence: 99%